A composition containing aromatic secondary amine alcohol and its application
By introducing aromatic secondary aminol into the optical resin material to form a crosslinked structure, the problem of low softening points of materials with a refractive index of 1.73 or above is solved, and the comprehensive performance improvement of high refractive index, heat resistance and low yellow index is achieved.
Patent Information
- Application Number
- CN202411909191.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, optical resin materials with a refractive index of 1.73 or above have low softening points, and the problems of high refractive index and low yellow index cannot be taken into account.
An aromatic secondary amine alcohol containing benzene ring, alcohol and amine structure is introduced to form a crosslinked structure by reacting with cyclic sulfur compounds and polythiols to improve the heat resistance and refractive index of the material.
The softening point of the optical material is significantly improved, the high refractive index of above 1.73 is maintained, while the heat resistance is improved and the yellow index is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical resins, and in particular to a composition containing an aromatic secondary amine alcohol and application thereof. Background Art
[0002] Compared with glass materials, optical resin materials have the advantages of low specific gravity, high impact toughness, not easy to break, comfortable to wear, easy processing, rich product series, easy to dye, etc., and are increasingly widely used in the optical lens market. The higher the refractive index, the thinner and lighter the lens, so improving the refractive index of the lens has become the direction of lens development. In order to achieve the preparation of high-refractive index optical resin materials, episulfide compounds and polythiols have become commonly used compositions. Currently, the above monomer compositions are used to prepare commercially available lenses with a refractive index of up to 1.70 and above.
[0003] Patent CN117050256A provides a thioether resin material system having high refractive index, high Abbe number, high heat resistance and controllable volume shrinkage, but the refractive index is only 1.68-1.69.
[0004] For the resin material with a refractive index of 1.70: In order to improve the heat resistance of the commercially available 1.70 lenses, a small amount of isocyanate is added to the composition, and the softening point is 88°C, but the refractive index is significantly reduced after addition. The method of using phenylenedimethyl mercaptan compounds shown in Japanese Patent Publication No. 2008-101190 achieves both high strength and high heat resistance, but the refractive index of the material is still relatively low.
[0005] For materials with a higher refractive index of 1.73 or above: The softening point of commercially available 1.74 lenses is lower than 80°C. In the patent CN104017216A, the inventors added a benzenedimethanethiol compound to a composition of an episulfide compound and S in order to provide an optical material that satisfies both high refractive index (ne is above 1.73) and high heat resistance, and finally achieved a softening point of 85°C for the material prepared by the composition. However, due to the use of component S to prepare the material, the yellow index was high, which limited the use of the material.
[0006] Compared with other refractive index materials, the softening point of materials with a refractive index of 1.73 or above has restricted the development of high refractive index materials under the condition that the refractive index does not decrease. Improving the softening point can prevent the material from deforming due to high temperature during use, which affects the performance of the material. Therefore, for optical materials with a refractive index of 1.73 or above prepared using episulfide compounds and polythiol compositions, how to improve the softening point and heat resistance is one of the problems that need to be solved urgently. Summary of the invention
[0007] In order to solve the problem in the prior art that the resin with a refractive index above 1.73 has a low softening point and cannot take into account both the refractive index and the yellowness index, the inventors have found through research that the introduction of an aromatic secondary amine alcohol containing a benzene ring, an alcohol and an amine structure can effectively solve the problem of the composition being not resistant to high temperatures and having a low refractive index after curing.
[0008] The curing process of the episulfide compound composition is a polymerization reaction of the ring-opening of the episulfide group, but this reaction releases a lot of heat, which in turn promotes the ring-opening reaction, causing the reaction in the curing process to be relatively concentrated, which can easily cause problems such as material grain and high yellow index after the episulfide compound composition is cured.
[0009] In the technical solution of the present application, aromatic secondary amine alcohol is selected as a component of the episulfide compound composition because amine compounds themselves have a catalytic effect, and the active hydrogen on the N of the aromatic primary amine alcohol compound is more likely to cause the system to polymerize too quickly and lead to explosion, and the active hydrogen on the N of the aromatic tertiary amine alcohol compound has a low catalytic effect; and the aromatic secondary amine alcohol compound can just solve the problem of concentrated ring-opening reaction of the episulfide compound composition.
[0010] The aromatic secondary amine alcohol is used in the present invention because the benzene ring has high stability and can improve the refractive index of the material. At the same time, the secondary amine group and alcohol group on the benzene ring are selected to react with the composition to form a cross-linked structure to improve the heat resistance. Moreover, N in the amine and O in the alcohol have strong polarity and can increase the density of the polar groups of the composition. In the solidified material, they combine with hydrogen atoms to form hydrogen bonds, thereby further improving the heat resistance of the material.
[0011] The specific technical solutions of the present invention are as follows: Firstly, a composition containing an aromatic secondary amine alcohol is provided, which mainly comprises an aromatic secondary amine alcohol, an episulfide compound and a polythiol; preferably, the composition comprises 5-10 parts of the aromatic secondary amine alcohol, 75-90 parts of the episulfide compound and 5-15 parts of the polythiol by weight.
[0012] Preferably, the aromatic secondary amine alcohol includes one or more of 2-acetamidophenol, 3-acetamidophenol, 4-acetamidophenol, 2-acetyl-4-butyrylaminophenol, and benzyl-2-acetamido-2-deoxy-α-D-pyranogalactoside.
[0013] Preferably, the episulfide compound includes one or more of bis(β-epithiopropyl)sulfide, bis(β-epithiopropyl)disulfide, bis(β-epithiopropyl)trisulfide, bis(β-epithiopropylthio)methane, 1,2-bis(β-epithiopropylthio)ethane, 1,3-bis(β-epithiopropylthio)propane, 1,4-bis(β-epithiopropylthio)butane, and bis(β-epithiopropylthioethyl)sulfide.
[0014] Preferably, the polythiol includes thiodiglycol, methanethiol, 1,2-ethanedithiol, 1,1-propanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 2,2-propanedithiol, 1,6-hexanedithiol, 1,2,3-propanetriol, 1,1-cyclohexanedithiol, 1,2-cyclohexanedithiol, 2,2-dimethylpropane-1,3-dithiol, 3,4-dimethoxybutane-1,2-dithiol, 2-dimethylcyclohexane-2,3-dithiol, 1,1-bis(mercaptomethyl)cyclohexane, 2,3-dithio(2-mercapto)-1-propanethiol, 2,3-dimercapto-1-propanol (2-mercaptoacetate), 2 ,3-dimercapto-1-propanol (3-mercaptopropionate), diethylene glycol bis(2-mercaptoacetate), diethylene glycol bis(3-mercaptopropionate), 1,2-dimercaptopropyl methyl ether, 2,3-dimercaptopropyl methyl ether, bis(2-mercaptoethyl) ether, ethylene glycol bis(2-mercaptoacetate), ethylene glycol bis(3-mercaptopropionate), trimethylolpropane bis(2-mercaptoacetate), pentaerythritol tetra(2-mercaptoacetate), pentaerythritol tetra(3-mercaptobutyrate), 1,1,2,2-tetra(mercaptomethylthio)ethane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6 ,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane, tetrakis(mercaptomethyl)methane, 2,5-dimercaptomethyl-1,4-dithiane, one or more of dipentaerythritol hexa(3-mercaptopropionate).
[0015] On the basis of the above scheme, the composition containing aromatic secondary amine alcohol preferably further contains a release agent, the mass of the release agent accounts for 0.0005-0.005 wt% of the total mass of the composition containing aromatic secondary amine alcohol, and the release agent is selected from one or more of lauryl alcohol polyoxyethylene ether phosphate, dibutyl phosphate, isotridecanol phosphate, and nonylphenol polyoxyethylene ether phosphate.
[0016] Secondly, the inventors further provide the use of the above-mentioned composition containing aromatic secondary amine alcohol in the preparation of optical materials, and the optical material can be obtained by polymerizing and curing the composition containing aromatic secondary amine alcohol under programmed temperature control.
[0017] Preferably, the programmed temperature control includes primary curing and secondary curing, wherein the temperature of the primary curing is 20-120° C.; the temperature of the secondary curing is 100-120° C., and the time is 2-4 h.
[0018] There is no special requirement for the time of primary curing, and the conventional temperature increase program in the art can be adopted. The preferred curing time is 10-30 h.
[0019] More specifically, the preparation method of the corresponding optical material comprises the following steps: (1) Preparing a composite mixture: adding an aromatic secondary amine alcohol to polythiol at 10°C-20°C and stirring to mix well, then adding an episulfide compound and a release agent, and mixing thoroughly to obtain a mixture; (2) Vacuum degassing: the mixture is subjected to vacuum degassing for 60-90 min at a vacuum degree of 0.05-2 torr under stirring conditions of 400-800 r / min; (3) Primary curing: pour the vacuum degassed mixture into a mold, and then place the mold in a programmed temperature curing furnace for primary curing; (4) Material mold opening: Use a special mold opener to open the mold; (5) Secondary curing: The molded lens is subjected to secondary curing in a programmed temperature curing oven.
[0020] Among them, vacuum degassing, primary curing, material mold opening and secondary curing are conventional methods in the art and have no obvious relevance to the improvement of the present invention, and will not be described in detail here.
[0021] The optical material prepared by using the composition containing aromatic secondary amine alcohol has a higher refractive index and softening point, the refractive index is 1.73-1.74, and the softening point can reach 90-100° C., and can be applied to the field of optical lenses.
[0022] The invention significantly improves the softening point of an optical material prepared by using the composition by adding aromatic secondary amine alcohol to the composition, improves heat resistance while maintaining a relatively high refractive index, and the benzene ring has relatively high stability. At the same time, the secondary amine group and the alcohol group on the benzene ring are selected to react with the composition to form a cross-linked structure to improve the heat resistance. Moreover, N in the secondary amine and O in the alcohol have very strong polarity, which can increase the density of the polar groups of the composition, and combine with hydrogen atoms in the solidified material to form hydrogen bonds, thereby further improving the heat resistance of the material. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the protection scope of the present invention.
[0024] The physical properties of the optical materials obtained below were tested according to the following methods: Heat resistance measurement: Using the heat deformation Vicat softening point tester XRW-300HB; cut out a sample with a length*width*thickness of 15*15*4mm, and while heating the sample from 20℃ at 2℃ / min, insert a standard indenter with a front cross-section of 1 mm2 into the thermoplastic plastic. A needle with a diameter of 1 mmΦ is inserted into the sample with a load of 1000g, and the softening point is measured when the indentation depth is 1mm.
[0025] Refractive index (ne): A sample with a length*width*thickness of 15*15*4 mm was prepared according to the above method, and the wavelength data of 546.1 nm (mercury green e-line) was tested at 20°C using Multi-wave length Abbe Refractometer DR-M4 (manufactured by ATTGO Co., Ltd.).
[0026] Yellowness index (YI value): Refer to the method in standard ASTM D:1925 to test performance.
[0027] Example 1 A composition containing aromatic secondary amine alcohol comprises 6.5 g of 2-acetamidophenol, 8.5 g of polythiol of pentaerythritol tris(3-mercaptopropionic acid) ester, 85 g of episulfide compound of bis(β-epithiopropyl) disulfide and 0.0008 g of lauryl alcohol polyoxyethylene ether phosphate release agent.
[0028] Example 2 A composition containing aromatic secondary amine alcohol comprises 6.5 g of 3-acetamidophenol, 8.5 g of polythiol of pentaerythritol tris(3-mercaptopropionic acid) ester, 85 g of episulfide compound of bis(β-epithiopropyl) disulfide and 0.0008 g of lauryl alcohol polyoxyethylene ether phosphate release agent.
[0029] Example 3 A composition containing aromatic secondary amine alcohol comprises 6.5 g of 4-acetamidophenol, 8.5 g of polythiol of pentaerythritol tris(3-mercaptopropionic acid) ester, 85 g of episulfide compound of bis(β-epithiopropyl) disulfide and 0.0008 g of lauryl alcohol polyoxyethylene ether phosphate release agent.
[0030] Example 4 A composition containing an aromatic secondary amine alcohol comprises 6.5 g of 2-acetyl-4-butyrylaminophenol, 8.5 g of a polythiol of pentaerythritol tris(3-mercaptopropionic acid) ester, 85 g of an episulfide compound of bis(β-epithiopropyl) disulfide and 0.0008 g of a lauryl alcohol polyoxyethylene ether phosphate release agent.
[0031] Example 5 A composition containing aromatic secondary amine alcohol comprises 8g of 3-acetamidophenol, 10g of polythiol of pentaerythritol tris(3-mercaptopropionic acid) ester, 82g of episulfide compound of bis(β-epithiopropyl) disulfide and 0.001g of lauryl alcohol polyoxyethylene ether phosphate release agent.
[0032] Example 6 A composition containing an aromatic secondary amine alcohol comprises 10 g of 2-acetyl-4-butyrylaminophenol, 8 g of a polythiol of pentaerythritol tris(3-mercaptopropionic acid) ester, 82 g of an episulfide compound of bis(β-epithiopropyl) disulfide and 0.003 g of a lauryl alcohol polyoxyethylene ether phosphate release agent.
[0033] Example 7 A composition containing aromatic secondary amine alcohol comprises 7g of 3-acetamidophenol, 7g of trimethylolpropane bis(2-thioglycolate) polythiol, 86g of bis(β-epithiopropyl) trisulfide episulfide compound and 0.004g of nonylphenol polyoxyethylene ether phosphate release agent.
[0034] Example 8 A composition containing an aromatic secondary amine alcohol comprises 5g of an aromatic secondary amine alcohol of 2-acetyl-4-butyrylaminophenol, 8g of a polythiol of 1,2,3-propanetrithiol, 90g of an episulfide compound of bis(β-epithiopropylthioethyl) sulfide and 0.004g of a nonylphenol polyoxyethylene ether phosphate release agent.
[0035] Comparative Example 1 An optical material composition comprises 6.5 g of p-aminophenol, 8.5 g of polythiol of pentaerythritol tris(3-mercaptopropionic acid) ester, 85 g of an episulfide compound of bis(β-epithiopropyl) disulfide and 0.0008 g of a lauryl alcohol polyoxyethylene ether phosphate release agent.
[0036] Comparative Example 2 An optical material composition comprises 3g of 3-acetamidophenol, 10g of polythiol of pentaerythritol tris(3-mercaptopropionate), 87g of an episulfide compound of bis(β-epithiopropyl) disulfide and 0.002g of a lauryl alcohol polyoxyethylene ether phosphate release agent.
[0037] Comparative Example 3 An optical material composition comprises 12g of 3-acetamidophenol, 7g of polythiol of pentaerythritol tris(3-mercaptopropionate), 81g of an episulfide compound of bis(β-epithiopropyl) disulfide and 0.001g of lauryl alcohol polyoxyethylene ether phosphate release agent.
[0038] Comparative Example 4 An optical material composition comprises 15 g of 2-acetyl-4-butyramide phenol, 6 g of 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane polythiol, 77 g of an episulfide compound of bis(β-epithiopropyl) disulfide and 0.005 g of lauryl alcohol polyoxyethylene ether phosphate release agent.
[0039] Application Examples 1-4 The optical materials were prepared using the compositions containing aromatic secondary amine alcohols of Examples 1-4 as raw materials, respectively, and the specific methods are as follows: (1) Preparing a composite mixture: at 10° C., according to the ratio described in Examples 1-4, firstly add the aromatic secondary amine alcohol to the polythiol and mix them evenly, then add the episulfide compound and the release agent and mix them thoroughly to obtain a composite mixture; (2) Vacuum degassing: The mixture obtained in step (1) was subjected to vacuum degassing (vacuum degree = 0.1 torr) for 60 min under stirring conditions at 600 r / min; (3) Primary curing: Place the vacuum degassed mixture into a mold, then place the mold in a programmed temperature curing oven at a controlled temperature of 20-120°C and cure for 15-25 hours to complete the primary curing. (4) Material mold opening: Use a special mold opener to open the mold; (5) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 120°C for secondary curing for 2 hours.
[0040] Application Example 5 The optical material is prepared using the composition containing aromatic secondary amine alcohol in Example 5 as a raw material, and the specific method is as follows: (1) According to the same method as in Application Examples 1-4, Example 5 was mixed according to the formula to obtain a mixture, and vacuum degassed according to the same method as in Application Examples 1-4. Then, the mold was placed in a programmed temperature curing furnace at a temperature of 20-100°C and cured for 30 hours to complete the primary curing. Then, the material was molded according to the same method as in Application Examples 1-4; (2) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 110°C for 3 hours for secondary curing.
[0041] Application Example 6 The optical material is prepared using the composition containing aromatic secondary amine alcohol in Example 6 as a raw material, and the specific method is as follows: (1) In the same manner as in Application Examples 1-4, Example 6 was mixed according to the formula to obtain a mixture, and vacuum degassing, primary curing and material mold opening were performed in the same manner as in Application Examples 1-4; (2) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 100°C for secondary curing for 4 hours.
[0042] Application Example 7 The optical material is prepared using the composition containing aromatic secondary amine alcohol in Example 7 as a raw material, and the specific method is as follows: (1) In the same manner as in Application Examples 1-4, Example 7 was mixed according to the formula to obtain a mixture, and vacuum degassing, primary curing and material mold opening were performed in the same manner as in Application Examples 1-4; (2) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 110°C for 3 hours for secondary curing.
[0043] Application Example 8 The optical material is prepared using the composition containing aromatic secondary amine alcohol in Example 8 as a raw material, and the specific method is as follows: (1) In the same manner as in Application Examples 1-4, Example 8 was mixed according to the formula to obtain a mixed material, and vacuum degassing, primary curing and material mold opening were performed in the same manner as in Application Examples 1-4; (2) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 100°C for secondary curing for 2 hours.
[0044] Comparative application example 1 The optical material composition of Comparative Example 1 was used as a raw material to prepare an optical material, and the specific method was as follows: (1) According to the same method as in Application Examples 1-4, the comparative example 1 is mixed according to the formula to obtain a mixed material, and vacuum degassing, primary curing and material mold opening are performed according to the same method as in Application Examples 1-4; (2) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 120°C for secondary curing for 2 hours.
[0045] Comparative Application Example 2 The optical material composition of Comparative Example 2 is used as a raw material to prepare an optical material, and the specific method is as follows: (1) According to the same method as in Application Examples 1-4, the comparative example 2 was mixed according to the formula to obtain a mixed material, and vacuum degassing, primary curing and material mold opening were performed according to the same method as in Application Examples 1-4; (2) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 120°C for secondary curing for 2 hours.
[0046] Comparative Application Example 3 The optical material composition of Comparative Example 3 was used as a raw material to prepare an optical material, and the specific method was as follows: (1) According to the same method as in Application Examples 1-4, Comparative Example 3 was mixed according to the formula to obtain a mixed material, and vacuum degassing, primary curing and material mold opening were performed according to the same method as in Application Examples 1-4; (2) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 100°C for secondary curing for 3 hours.
[0047] Comparative Application Example 4 The optical material composition of Comparative Example 4 was used as a raw material to prepare an optical material, and the specific method was as follows: (1) According to the same method as in Application Examples 1-4, the comparative example 4 was mixed according to the formula to obtain a mixed material, and vacuum degassing, primary curing and material mold opening were performed according to the same method as in Application Examples 1-4; (2) Secondary curing: The molded lens is placed in a programmed temperature curing oven at 110°C for secondary curing for 2 hours.
[0048] Experimental Example 1 The optical materials obtained from Application Examples 1-8 and Comparative Application Examples 1-4 were subjected to performance tests, and the test results are shown in Table 1.
[0049] Table 1 Performance test results of optical materials of application examples 1-8 and comparative application examples 1-4 It can be seen from the data in Table 1 that a certain amount of aromatic secondary amine alcohol is added in the embodiments, so that a high refractive index of more than 1.73 is maintained; the softening point temperature of the optical resin material in Examples 1-8 is significantly higher than that of Comparative Example 2 when the refractive index is higher than 1.73; although excessive addition of aromatic secondary alcohol amine can achieve a higher softening point, the refractive index is lower than 1.73 and the yellow index increases, resulting in poor overall comprehensive performance, so the addition amount of aromatic secondary amine alcohol needs to be controlled within a reasonable range; and the addition of other amine substances (such as Comparative Application Example 1) obviously causes problems such as material grain in the system.
[0050] It can be seen that the composition of the present invention has obvious advantages, and a high-refractive index resin material with good heat resistance is obtained. The softening point of the material can be significantly improved while maintaining a high refractive index and a low yellow index. The resin material prepared by the present invention has made significant progress in the composition containing episulfide compounds, which has the significance and value of guiding industrial production and application.
[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composition containing an aromatic secondary amine alcohol, mainly comprising an episulfide compound and a polythiol, characterized in that: Also included are aromatic secondary amine alcohols; The composition comprises 5-10 parts of aromatic secondary amine alcohol, 75-90 parts of episulfide compounds and 5-15 parts of polythiol by weight.
2. The composition containing aromatic secondary amine alcohol according to claim 1, characterized in that: The aromatic secondary amine alcohol includes one or more of 2-acetamidophenol, 3-acetamidophenol, 4-acetamidophenol, 2-acetyl-4-butyrylaminophenol, and benzyl-2-acetamido-2-deoxy-α-D-pyranogalactoside.
3. The composition containing aromatic secondary amine alcohol according to claim 1, characterized in that The episulfide compound includes one or more of bis(β-epithiopropyl) sulfide, bis(β-epithiopropyl) disulfide, bis(β-epithiopropyl) trisulfide, bis(β-epithiopropylthio) methane, 1,2-bis(β-epithiopropylthio) ethane, 1,3-bis(β-epithiopropylthio) propane, 1,4-bis(β-epithiopropylthio) butane, and bis(β-epithiopropylthioethyl) sulfide.
4. The composition containing aromatic secondary amine alcohol according to claim 1, characterized in that The polythiol includes thiodiglycol, methanethiol, 1,2-ethanedithiol, 1,1-propanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 2,2-propanedithiol, 1,6-hexanedithiol, 1,2,3-propanetriol, 1,1-cyclohexanedithiol, 1,2-cyclohexanedithiol, 2,2-dimethylpropane-1,3-dithiol, 3,4-dimethoxybutane-1,2-dithiol, 2-dimethylcyclohexane-2,3-dithiol, 1,1-bis(mercaptomethyl)cyclohexane, 2,3-dithio(2-mercapto)-1-propanethiol, 2,3-dimercapto-1-propanol (2-mercaptoacetate), 2 ,3-dimercapto-1-propanol (3-mercaptopropionate), diethylene glycol bis(2-mercaptoacetate), diethylene glycol bis(3-mercaptopropionate), 1,2-dimercaptopropyl methyl ether, 2,3-dimercaptopropyl methyl ether, bis(2-mercaptoethyl) ether, ethylene glycol bis(2-mercaptoacetate), ethylene glycol bis(3-mercaptopropionate), trimethylolpropane bis(2-mercaptoacetate), pentaerythritol tetra(2-mercaptoacetate), pentaerythritol tetra(3-mercaptobutyrate), 1,1,2,2-tetra(mercaptomethylthio)ethane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6 ,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane, tetrakis(mercaptomethyl)methane, 2,5-dimercaptomethyl-1,4-dithiane, one or more of dipentaerythritol hexa(3-mercaptopropionate).
5. The composition containing aromatic secondary amine alcohol according to claim 1, characterized in that: The composition containing aromatic secondary amine alcohol also includes a release agent, the mass of which accounts for 0.0005-0.005 wt% of the total mass of the composition containing aromatic secondary amine alcohol, and the release agent is selected from one or more of lauryl alcohol polyoxyethylene ether phosphate, dibutyl phosphate, isotridecanol phosphate, and nonylphenol polyoxyethylene ether phosphate.
6. Use of the composition containing aromatic secondary amine alcohol according to any one of claims 1 to 5 for preparing optical materials, characterized in that: The composition containing the aromatic secondary amine alcohol is polymerized and cured under programmed temperature control to obtain an optical material.
7. Use of the composition containing aromatic secondary amine alcohol according to claim 6 in preparing optical materials, characterized in that: The program temperature control includes primary curing and secondary curing, wherein the temperature of the primary curing is 20-120°C and the time is 10-30 hours; the temperature of the secondary curing is 100-120°C and the time is 2-4 hours.
8. Use of the composition containing aromatic secondary amine alcohol according to claim 6 in preparing optical materials, characterized in that: The method for preparing the optical material comprises the following steps: (1) Preparing a composite mixture: adding an aromatic secondary amine alcohol to polythiol at 10°C-20°C and stirring to mix well, then adding an episulfide compound and a release agent, and mixing thoroughly to obtain a mixture; (2) Vacuum degassing: the mixture is subjected to vacuum degassing for 60-90 min at a vacuum degree of 0.05-2 torr under stirring conditions of 400-800 r / min; (3) Primary curing: pour the vacuum degassed mixture into a mold, and then place the mold in a programmed temperature curing furnace for primary curing; (4) Material mold opening: Use a special mold opener to open the mold; (5) Secondary curing: The molded lens is subjected to secondary curing in a programmed temperature curing oven.
9. Use of the composition containing aromatic secondary amine alcohol according to claim 6 in preparing optical materials, characterized in that: The prepared optical material has a refractive index of 1.73-1.74 and a softening point of 90-100°C.
Citation Information
Patent Citations
Composition for use in optical material with high refractive index and high strength
CN104017216A
Composition for high-refractive index and high-strength resin
JP2008101190A